Effects of Sodium Bicarbonate on High-Intensity Endurance Performance in Cyclists: A Double-Blind, Randomized Cross-Over Trial - Egger, Florian; Meyer, Tim; Such, Ulf; Hecksteden, Anne (PLOS ONE, 2014)
Background While the ergogenic effect of sodium bicarbonate (BICA) on short-term, sprint-type performance has been repeatedly demonstrated, little is known about its effectiveness during prolonged high-intensity exercise in well-trained athletes. Therefore, this study aims to examine the influence of BICA on performance during exhaustive, high-intensity endurance cycling. Methods This was a single-center, double-blind, randomized, placebo-controlled cross-over study. Twenty-one well-trained cyclists (mean ± SD: age 24±8 y, BMI 21.3±1.7, VO2peak 67.3±9.8 ml·kg−1·min−1) were randomly allocated to sequences of following interventions: oral ingestion of 0.3 g·kg−1 BICA or 4 g of sodium chloride (placebo), respectively. One h after ingestion subjects exercised for 30 min at 95% of the individual anaerobic threshold (IAT) followed by 110% IAT until exhaustion. Prior to these constant load tests stepwise incremental exercise tests were conducted under both conditions to determine IAT and VO2peak. Analysis of blood gas parameters, blood lactate (BLa) and gas exchange measurements were conducted before, during and after the tests. The main outcome measure was the time to exhaustion in the constant load test. Results Cycling time to exhaustion was improved (p<0.05) under BICA (49.5±11.5 min) compared with placebo (45.0±9.5 min). No differences in maximal or sub-maximal measures of performance were observed during stepwise incremental tests. BICA ingestion resulted in an increased pH, bicarbonate concentration and BLa before, throughout and after both exercise testing modes. Conclusion The results suggest that ingestion of BICA may improve prolonged, high-intensity cycling performance. Trial Registration German Clinical Trials Register (DRKS) DRKS00006198.